Podcasts in the Chemistry Teaching - Leite, Bruno Silva (Orbital: The Electronic Journal of Chemistry, 2016)
Information and Communication Technologies (ICT) provide facilities in teaching through education. There are many new tools and methodologies that use ICT as a knowledge-building support, but that are not always related to pedagogical practice. The Podcast is an important technology that can be used in the classroom. Using this tool, it can make the most interactive chemistry class, fleeing the classroom routine. However, it is necessary to point out that the podcast is just one feature that should be incorporated into education and not a substitute. This paper describes the development of Chemistry Podcasts by teachers and chemistry students in three disciplines in 2015. This study took place over a one-year period in a public University, in Pernambuco, Brazil. In the discipline of "Computer applied to the teaching of chemistry" participated 21 Chemistry teachers. In the disciplines of "Information and Communication Technologies in the teaching of chemistry" and "Informatics, Chemistry and Education" was composed of 54 undergraduate students in chemistry. Twelve podcasts were elaborated by students and five by teachers in this paper we present only nine. The results showed the contribution of podcasts produced by teachers and students in teaching and learning process chemistry.DOI: http://dx.doi.org/10.17807/orbital.v0i0.898